Význam Arktidy v mezinárodních vztazích - Kopečná, Anna (Univerzita Karlova, Fakulta sociálních věd, 2011)
In recent years several factors changed the importance of the Arctic in international relations. Firstly, the rapid melting of Arctic ice cover opened potential access to vast natural resources within the Arctic Ocean seabed. It is estimated that the Arctic may contain one quarter of world's undiscovered reserves of oil and gas. Secondly, the water ways along the Russian and Canadian northern coasts became ice-free, although so far just for few days every year. Should the Arctic Ocean continue to melt, then in several decades the Northern Sea Route and the Northwest Passage could become navigable for greater part of the year. This would shorten the journey distance from Europe to Asia by as much as forty percent, thereby cutting travel times and shipping costs. Finally, as the Arctic does not belong to any single country, there has been an increasing interest among the Arctic rim states, which have been working on delineating their maritime boundaries in order to ensure their territorial claims. This process has proceeded in accordance with the international legal framework as established by the 1982 United Nations Convention on the Law of the Sea (UNCLOS). Coastal states are entitled to a 200-nautical mile exclusive economic zone (EEZ) around their coastline. However, should they be able to prove. V poslední době se díky několika faktorům změnil význam Arktidy v mezinárodních vztazích. Zaprvé, tání arktického ledu umožňuje snazší přístup k rozsáhlým přírodním zdrojům, nacházejících se pod dnem Severního ledového oceánu. Odhaduje se, že v Arktidě se může nacházet až čtvrtina dosud neobjevených zásob ropy a zemního plynu na světě. Zadruhé, ledová pokrývka na námořních trasách podél severního pobřeží Ruska a Kanady roztála, i když zatím pouze na pár dní v roce. Pokud se bude Severní ledový oceán nadále oteplovat, pak by Severovýchodní a Severozápadní cesta mohly být průjezdné po většinu roku. Tím by se zkrátily dosavadní plavební trasy z Evropy do Asie o 40 procent a obchodním společnostem by se ušetřil čas i ...